Synthesis of porous materials for cooling and gas storage applications - Wong, Shina Si Jing (2015)
Metal organic frameworks (MOFs) are porous three dimensional structures formed by inorganic connectors such as chromium and organic linkers such as terephthalic acid. MOFs are studied as their properties make them suitable for use in various applications such as gas storage. MOFs can be used in Adsorbed Natural Gas (ANG), which can be an alternative to Compressed Natural Gas (CNG) and Liquefied Natural Gas (LNG). Not only CNG is bulky and expensive and LNG is not convenient due to handling of cryogenic fuel, their energy density is low as compared to gasoline. In this project, the focus will be MIL-101 (Cr) (Material Institut Lavoisier) and the adsorption of methane. Although previous researches have been conducted on the adsorption capabilities of MIL-101 (Cr), few researches have been done using doped MIL-101 (Cr) at different concentration. Hence, the objective of this project is to synthesise virgin and doped MIL-101 (Cr) so as to study the properties and applications of it. Tests were carried out through Scanning Electron Microscopy (SEM), Energy Dispersive Spectrometry (EDS), Powder X-ray Diffraction (XRD), Thermogravimetric Analyzer (TGA) and Nitrogen Adsorption/Desorption. It was found that the morphology changed at the doping of Sodium and Potassium ions at 40% concentration. Also, doped samples have higher thermal stability than virgin samples. In addition, the surface areas of samples decreases with higher concentration of doping. From the experimental results of Methane adsorption, the adsorption is faster at lower temperatures and high pressure.